Foreign direct investment into BRICS: an empirical analysis. Issue 1 (2nd January 2020) - Maryam, Javeria; Mittal, Ashok
Abstract: This paper examines empirically the role of selected macro-economic variables in determining FDI inflows in the context of BRICS countries. The study employed the Pooled Mean Group (PMG) Auto-Regressive Distributive Lag (ARDL) method for annual dataset over the period 1994 to 2018. The findings of the study indicate that factors like GDP, trade openness, exchange rate, gross capital formation and availability of infrastructure facilities are significant in long run. The country-specific analysis for short run indicates that among BRICS, the FDI determining variables differ in each country. Among BRICS, China is the finest country with the significant and positive effects of examined variables in stimulating FDI inflows. As BRICS economies are facing challenge at the global level, the study suggested the need of adoption of liberal policies to attract more FDI along with growth promotion.